N‐myc downstream regulated family member 1 (NDRG1) is enriched in myelinating oligodendrocytes and impacts myelin degradation in response to demyelination. Issue 2 (23rd October 2021) - Marechal, Damien; Dansu, David K.; Castro, Kamilah; Patzig, Julia; Magri, Laura; Inbar, Benjamin; Gacias, Mar; Moyon, Sarah; Casaccia, Patrizia
Abstract: The N‐myc downstream regulated gene family member 1 ( NDRG1 ) is a gene whose mutation results in peripheral neuropathy with central manifestations. While most of previous studies characterized NDRG1 role in Schwann cells, the detection of central nervous system symptoms and the identification of NDRG1 as a gene silenced in the white matter of multiple sclerosis brains raise the question regarding its role in oligodendrocytes. Here, we show that NDRG1 is enriched in oligodendrocytes and myelin preparations, and we characterize its expression using a novel reporter mouse ( TgNdrg1‐EGFP ). We report NDRG1 expression during developmental myelination and during remyelination after cuprizone‐induced demyelination of the adult corpus callosum. The transcriptome of Ndrg1‐EGFP+ cells further supports the identification of late myelinating oligodendrocytes, characterized by expression of genes regulating lipid metabolism and bioenergetics. We also generate a lineage specific conditional knockout ( Olig1 cre/+ ;Ndrg1 fl/fl ) line to study its function. Null mice develop normally, and despite similar numbers of progenitor cells as wild type, they have fewer mature oligodendrocytes and lower levels of myelin proteins than controls, thereby suggesting NDRG1 as important for the maintenance of late myelinating oligodendrocytes. In addition, when control and Ndrg1 null mice are subject to cuprizone‐induced demyelination, we observe a higher degree of demyelination in the mutants. Together these data identify NDRG1 as an important molecule for adult myelinating oligodendrocytes, whose decreased levels in the normal appearing white matter of human MS brains may result in greater susceptibility of myelin to damage. MAIN POINTS: NDRG1 is a gene regulated by DNA methylation in oligodendrocytes Ndrg1‐EGFP reporter mice label oligodendrocytes in developing and adult brains Ndrg1 null mice show increased myelin loss after cuprizone treatment.